2007
DOI: 10.1037/0278-6133.26.1.30
|View full text |Cite
|
Sign up to set email alerts
|

A transdisciplinary model integrating genetic, physiological, and psychological correlates of voluntary exercise.

Abstract: Objective-Physical inactivity contributes to as many as 250,000 premature deaths per year (R. R. Pate et al., 1995). The authors' objective was to test a transdisciplinary model of the ways in which genetic variants, physiological factors, and psychological factors are thought to influence exercise with 64 healthy, regular exercisers.Design-In a within-subjects design, psychological and physiological responses to exercise were compared with responses to a sedentary activity.Main Outcome Measures-The authors me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
149
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(161 citation statements)
references
References 61 publications
10
149
1
1
Order By: Relevance
“…Notably, however, we did not find evidence that the relationship between BDNF genotype and the behavioral measure of intrinsic motivation is mediated by affective valence or positive affective response during the exercise, as BDNF genotype was not related to affective response in the current study. This finding is inconsistent with the results of Bryan et al (2007), who found that those with a met allele had a greater positive affective response to exercise. This may be due to a key methodological difference; in the Bryan et al study, exercise intensity was objectively controlled (at 65% of individual's predetermined VO2max), whereas participants in the current study chose the pace they felt was of a moderate intensity.…”
Section: Intrinsic Motivation and Bdnf Snp 22contrasting
confidence: 57%
See 3 more Smart Citations
“…Notably, however, we did not find evidence that the relationship between BDNF genotype and the behavioral measure of intrinsic motivation is mediated by affective valence or positive affective response during the exercise, as BDNF genotype was not related to affective response in the current study. This finding is inconsistent with the results of Bryan et al (2007), who found that those with a met allele had a greater positive affective response to exercise. This may be due to a key methodological difference; in the Bryan et al study, exercise intensity was objectively controlled (at 65% of individual's predetermined VO2max), whereas participants in the current study chose the pace they felt was of a moderate intensity.…”
Section: Intrinsic Motivation and Bdnf Snp 22contrasting
confidence: 57%
“…Due to the small number of participants with the met/met genotype, we collapsed across those with at least one copy of the met allele for between group comparisons as has been done in prior work (e.g., Bryan, et al, 2007;Bryan, et al, 2013;Gatt et al, 2009;Hariri et al, 2003;Jiang et al, 2013) and as is consistent with research on the BDNF SNP more broadly (Anastasia et al, 2013;Egan et al, 2003a;Kleim et al, 2006;Pezawas et al, 2004b;Szeszko et al, 2005).…”
Section: Intrinsic Motivation and Bdnf Snp 13mentioning
confidence: 98%
See 2 more Smart Citations
“…Consistent with established procedures 15,44 and our prior work, 45 Vo 2 max was assessed via online computer-assisted open-circuit spirometry during incremental treadmill exercise (Trackmaster 425 treadmill, Newton, KS). Oxygen levels were assessed using the Medgraphics Cardi02=CP system (St. Paul, MN).…”
Section: Methodsmentioning
confidence: 99%